Experimental study of masonry wall exposed to blast loading - Ahmad, S; Elahi, A; Pervaiz, H; Rahman, A; Barbhuiya, Salim (Eduardo Torroja Institute for Construction Science, 2013)
The challenge of protecting the nation against the attack of terrorism has raised the importance to explore the understanding of building materials against the explosion. Unlike most of the building materials, brick masonry materials offer relatively small resistance against blast loading. In this research, a brick masonry wall was exposed to varying blast load at different scaled distances. Six tests with different amounts of explosives at various distances were carried out. Pressure time history, acceleration time history and strain at specific location were measured. The parameters measured from experimental pressure time history and acceleration time history is compared with those determined by ConWep to establish the correlations between experimental determined records and ConWep values. The experimental results were also compared with some researchers. These correlations may assist in understanding the behaviour of masonry structures subjected to explosive loading.